Edaphic patchiness influences grassland regeneration from the soil seed bank in mountain grasslands of central Argentina - Funes, Guillermo (2001)
The soil seed- banks in the main natural vegetation patches that makes up mountain grasslands on granite substrates in central Argentina were studied. The main natural vegetation types are moist swards, tall- tussock grasslands and stony grasslands. Ten compoun soil samples from each community at two soil depths from each community at two soil dephts (0-5 and 5-40 dm) were taken, The density of soil seed- banks was highest in moist swards, intermediate in stony grasslands and lowest in tall- tussock grasslands. Low levels of similarity were found between the established vegetation and total soil seed- band in tall- tussock grasslands and stony grasslands, but the similarity was higher in swards. In all three communities the seed- bank was most freqauently transient in nature. Short- term persistent and longterm persistent seed- banks were less frequent. Regeneration from the seed- bans after disturbance is expeted to differ among communities on different edaphic patches. On the basis of the density and longevity of the soil seed banks and the similarity to the established vegetation, potential for in sity regeneration should be lower in tall tussoc grasslands, intermediate in stony grasslands an higher in moist swards.